2019
DOI: 10.1021/acs.cgd.8b01709
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Coordination To Dramatically Enhance the Stability of In-MOF for Selectively Capturing CO2 from a CO2/N2 Mixture

Abstract: Two In-based metal−organic frameworks (MOFs) have been designed and synthesized by the reaction of 3phenylpyridine polycarboxylic ligands and In 3+ cations: In 3 L 1 4 •(CH 3 NH 2 CH 3 ) 3 (H 3 L 1 = 5-(3′,5′-dicarboxylphenyl)nicotic acid; 1) and In 2 L 2 2 (CH 3 COO) 2 •(CH 3 ) 2 NH 2 •(CH 3 ) 3 NH•H 2 O (H 3 L 2 = 3-(2,4-dicarboxylphenyl)-6-carboxylpyridine;2). Singlecrystal X-ray diffraction analysis indicates that the In 3+ centers in 1 are all coordinated by eight oxygen atoms from four carboxylate groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Moreover, the residual M could effectively prevent the interaction between N 2 and frameworks . Furthermore, Zhang et al built an In-based MOFs (In 3 L 1 159 4 ·(CH 3 NH 2 CH 3 ) 3 ) via 5-(3′,5′-dicarboxylphenyl)­nicotic acid (H 3 L 1 159 ) (Figure ). In this structure, a per In 3+ ion was coordinated with eight oxygen atoms from four carboxylate groups, which formed two different channels with the sizes of 14.4 Å × 8.75 Å and 7.24 Å× 6.7 Å.…”
Section: Co2/n2mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the residual M could effectively prevent the interaction between N 2 and frameworks . Furthermore, Zhang et al built an In-based MOFs (In 3 L 1 159 4 ·(CH 3 NH 2 CH 3 ) 3 ) via 5-(3′,5′-dicarboxylphenyl)­nicotic acid (H 3 L 1 159 ) (Figure ). In this structure, a per In 3+ ion was coordinated with eight oxygen atoms from four carboxylate groups, which formed two different channels with the sizes of 14.4 Å × 8.75 Å and 7.24 Å× 6.7 Å.…”
Section: Co2/n2mentioning
confidence: 99%
“…Structures of H 3 L 1 159 and H 3 L 2 159 with different positions of carboxyl groups. Reprinted with permission from Peng et al, American Chemical Society, Copyright 2019.…”
Section: Co2/n2mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, thousands of MOFs have been synthesized, some of which have been utilized in the attempt to capture CO 2 from the air. Peng et al [28] designed and synthesized 2 incorporated MOFs to study their stability and ability to capture CO 2 from the air. Liu et al [11] used an amine-functionalized MOF and an ultra-microporous MOF to capture CO 2 directly from the air, and further investigated the performance of CO 2 capture and the reproducibility of MOFs under humid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) have been extensively used as porous materials in many fields due to the advantages of combining organic and inorganic materials, as well as due to their adjustable structures and functional pore environment. Although a large number of research studies have shown potential application prospects of MOFs, their practical application undergoes some challenges, such as their typically poor stability, especially in water. , Recent advances have confirmed the success of using carboxylate-N-heterocyclic ring ligands to construct stable MOFs in which the rich-N azolate groups not only provide potential basic sites but also form rigid coordination bonds and where carboxylate units possess flexible coordinated modes . Besides this, metal ions are also important in the construction of stable MOFs; the high-oxidation-state Zr 4+ , Ti 4+ Cr 3+ , Fe 3+ , Al 3+ , and In 3+ ions can easily generate MOFs that are stable in acid, base, and water. The In-MOFs are especially interesting and important because In 3+ ions can form various building blocks including {InO/OH} clusters and infinite chain units, producing versatile stable frameworks. , According to the hard–soft acid–base (HSAB) theory, most In 3+ ions tend to coordinate with the carboxylic acid oxygen atoms to form In-based 2D and 3D MOFs. , However, recent studies have found that In–N bonds are very favorable to generate stable MOFs, , but the design and synthesis of In-MOF materials containing In–N bonds are still in their infancy.…”
Section: Introductionmentioning
confidence: 99%